The features of distribution of microelements in surface deposits of Galindez Island (Western Antarctica) - S. M. Nedogibchenko; N. O. Kryuchenko; E. Y. Zovinskiy (Ukrainian Antarctic Journal, 2013)
It was considered features of distributing of chemical elements in the surface deposits of the offshore Antarctic oasis of the Galindez island (Western Antarctic Region). It was set the heighten content in them As, Sr and Sd, and also close cross-correlation connection (more than 0,9) between the group of heavy metals – Cu, Zn, Cd and Se. The change of content of heavy metals on the profile of Woozly Hill is determined – Ni and Co accumulate on the top of the hill (first ledge); distributing of Zn is unevenly on all slope; maximal content of Fe and Pb is on the last ledge. The Clarke of concentration of heavy metals (Zn, Cu, Co, Ni, Pb) is calculated and it was set, that Co, Ni, Pb are inclined to flux from maternal rocks and accumulate in surface deposits in the row: Pb > Co > Ni, but Zn and Cu concentrate in maternal rocks.